STRATEGI PARTAI GOLKAR DALAM MEMPERTAHANKAN SUARA TERBANYAK PADA PEMILIHAN LEGISLATIF TAHUN 2014 DI KABUPATEN KAMPAR - Ardian, Niko; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Golkar Party Kampar regency was the winning party in the 2009 legislative elections. In 2014 the Golkar party won the winning party by winning the most seats, 9 seats in the Kampar Kabupetan DPRD, despite losing 2 seats from the previous legislative election and having to face the Democratic party which is the party The Kampar Regent at the time, however, the Golkar party was able to become the winning party in the 2014 Kampar district legislative elections.            The formulation of the problem in this study is "How is the strategy of the Golkar Party to maintain its victory in the 2014 Legislative Election in Kampar District and what is the impact of the strategy on the Golkar party vote in the 2014 Legislative Election in Kampar District". The purpose of the study was to analyze the strategy of the Golkar Party in the 2014 legislative elections and determine the impact of the strategies implemented in the 2014 legislative elections in Kampar District. This research is a descriptive study with a qualitative approach. The location of this research was conducted in DPD II of the Golkar Party in the Kampar Regency. Data collection techniques are done by qualitative data analysis.            The results of this study indicate that the Kampar Regency Golkar Party won the battle in the 2014 Legislative elections in Kampar Regency and placed its cadres as the highest Leaders in the Kampar Regency DPRD and could carry the Kampar Regency Regent candidates without having to form a coalition with other parties in the upcoming Pilkada.Keywords: Golkar Party, Strategy, Legislative